Influence of an inclined thick partition on free convection heat transfer performance under surface radiation in a hollow block - Bondareva, Nadezhda S.; Gibanov, Nikita S.; Miroshnichenko, Igor V.; Öztop, Hakan Fehmi; Sheremet, Mikhail A. (Taylor & Francis Inc, 2026)
In the present work, a computational analysis of the combined energy transfer by free convection, radiation, and heat conduction in 2D hollow block with an inclined partition was carried out. The inclined partition was made of a heat-conducting material and had a finite thickness. The closed space inside the brick was filled with air (Pr = 0.71) and the airflow is laminar. The external surfaces of the vertical borders are considered to be isothermal, and the remaining horizontal surfaces are supposed to be adiabatic. The finite difference technique is employed to work out numerically the differential equations. The in-house computational code was verified in detail using various problems. The major characteristics that determine the considered phenomena are surface emissivity of internal walls, Ra number, and material of solid walls and partition. As a result of the research, the distributions of streamlines and isotherms combined with the average Nusselt numbers were obtained. Depending on the material of the partition, the flow structure in the cavity changes significantly, which reflects the distribution of streamlines, namely, for the materials with low thermal conductivity the convective cell in the upper part of the cavity is elongated, while in the lower part it is shifted to the lower and left borders. The isotherms reflect the more intensive heating in the left part of the area. With an increase in the thermal conductivity coefficient, the streamlines reflecting the nature of the flow are restructured. It was shown that the presence of an inclined partition significantly reduces the intensity of convective heat transfer.
Keywords: Conjugate natural convection; finite difference method; hollow brick; non-primitive variables; numerical simulation; streamlines and isotherms; surface radiation; thick heat-conducting partition